The role of international medical graduates in America's small rural critical access hospitals. - Hagopian, A; Thompson, M; Kaltenbach, E; Hart, L (2004)
CONTEXT: Critical access hospitals (CAHs) are a federal Medicare category for isolated rural facilities with 15 or fewer acute care beds that receive cost-based reimbursement from Medicare. PURPOSE: This study examines the role of foreign-born international medical graduates (IMGs) in the staffing of CAHs. METHODS: Chief executive officers (CEOs) of CAH facilities answered a telephone survey on their use of IMGs and the characteristics of those IMGs in winter 2002 (388 responded, for a 96% response rate). This descriptive report presents roles and characteristics of IMGs in CAH facilities and the opinions of the CEOs about these practitioners. FINDINGS: Overall, 1 (24%) in 4 admitting physicians in CAHs are graduates of non-US medical schools (compared with 23% of physicians nationally), although the rates are higher for CAHs in persistent poverty counties, CAHs that report recruitment problems, and CAHs with smaller medical staffs. Hospitals east of the Mississippi River are more heavily reliant on IMGs than hospitals in the west. Most IMGs are internists (59%) and most (61%) come from India, the Philippines, or Pakistan. Hospital administrators rate the clinical skills of their IMGs highly and their interpersonal skills only slightly lower. Almost half of CAH administrators said their communities recruited their first IMGs during or after 1994, the year of pro-IMG legislative changes. CONCLUSION: IMG physicians play a significant and possibly growing role in staffing CAHs.